Advances in research and development : heterojunctions for high-speed and infrared applications - Francombe, Maurice H.; Vossen, John L. (Thin films (San Diego, Calif.), 1998)
Significant progress has occurred during the last few years in device technologies and these are surveyed in this new volume. Included are Si/(Si-Ge) heterojunctions for high-speed integrated circuits, Schottky-barrier arrays in Si and Si-Ge alloys for infrared imaging, III-V quantum-well detector structures operated in the heterodyne mode for high-data-rate communications, and III-V heterostructures and quantum-wells for infrared emissions.